Sharia stocks optimal portfolio analysis using single index model - Gatot Hendra Prakoso; Bambang Santoso Marsoem (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This study is aimed to analyze the optimal portfolio of Jakarta Islamic Index within December 2016 to November 2019 period. The research samples that were being used in this study were the stocks that are consistently included in JII during the study period. This research is a descriptive study using the Single Index Model. Of the nineteen JII sample stocks, an optimal portfolio was formed with nine stocks as constituents, namely: ASII (6.12%), ASRI (2.37%), ICBP (24.60%), INCO (5.09%), INTP (11.45%), KLBF (2.03%), SMGR (16.91%), UNTR (19.58%) and UNVR (11.83%). The conclusion of this research is that the optimal portfolio expected return of JII shares is 1.1180% and 1.11%. The risk of the formed portfolio was up to 6.89%. The optimal portfolio can be said to be suitable for investment because the expected return of both of them is greater than the expected market return (JII) which during the study period was 0.00104, or 1.04%.